Pathogenic polypores in Argentina - Rajchenberg, Mario (2013)
We surveyed the polypore species associated with living hosts in Argentina. We reviewed the literature on polypores found in Argentina and, in addition with the study of unpublished herbarium material, present a list of 87 species decaying living trees in native forests and introduced plantations. The rot type, host(s), distribution and remarks are presented for each species. Among 87 species found, 71 produce a white rot and 16 a brown rot in wood; 61 species were exclusively found on native hosts and 7 on exotic, cultivated hosts, while 18 were found on both types of substrates; one species, Amylosporus campbellii, was exclusively found associated with grasses. For most cases, there are no pathological studies based on rot measurement and culture isolation to determine incidence and severity of the decay.